Families of the Past: Was the North-Western European Household System Prevalent in the 19th Century Lithuania? - Maslauskaitė, Aušra; Leinartė, Dalia; Dirsytė, Irma (Sociologija. Mintis ir veiksmas, 2021)
The paper analyzes family and household types in the mid. 19th century Vilnius and Kaunas gubernijy. The research is based on the large-scale dataset composed of the archival census-like listings of individuals by family units and defined as inventories. The dataset covers the inventories from 1847 and it includes around 20 thousand individuals. Based on the Hammel and Laslett (1974) methodology the research identifies nuclear, extended, and multiple-family households. The research is guided by Hajnal’s (1982) theory on the North-Western and Eastern European household systems. The former could be characterized by the dominance of the nuclear family households. Empirical analysis proves that around 40 percent of all households were nuclear family households. On the other hand, multiple-family households were not dominant. Thus, the main findings corroborate the idea that there was a transitional zone between the Eastern and North-Western household systems in the western part of the tsarist Russian empire.
Keywords: households; families; 19th century Lithuania; historical demography